Hazard Identification, Risk Assessment, and Risk Control (HIRARC) di PT. X - David Christanto; Kriswanto Widiawan (Jurnal Titra, 2022)
PT. X is a company engaged in manufacturing, namely as a producer of expanded metal and hollow. So far, the company has not implemented K3 properly in its company. Therefore, the purpose of this final project is to identify hazard risks, assess the level of risk, and provide risk control proposals (HIRARC) in the company's production process. In the initial stage of this final project, the authors will conduct direct observations in the field and interviews with field supervisors and workers. After conducting interviews and observations, the authors will identify hazards, assess the risks of hazards, and provide suggestions for controlling the risks of hazards. The results obtained from the analysis are that there are 24 potential hazards that have a significant risk rating category, 8 moderate risk ratings, and 4 low risk rating. The risk controls provided are 4 technical engineering, 43 administrative steps, and 5 PPE. After the risk control is implemented, it is estimated that the risk rating will change to a lower level.